Intraspecific and Interstage Similarities in Host-Plant Preference in the Diamondback Moth (Lepidoptera: Plutellidae) - Francisco Rubén Badenes-Pérez; David G. Heckel (Horticulturae, 2022)
The diamondback moth, Plutella xylostella L. (Lepidoptera: Plutellidae), is an important insect pest of cruciferous crops. Understanding its preference patterns can lead to more efficient management methods, such as trap crops. Several strains of P. xylostella were used to test whether there were differences in oviposition preference in a four-choice setting, on abaxial versus adaxial leaf surfaces in 28 different plant species, and on substrates with different concentrations of sinigrin (allylglucosinolate). Additionally, the larval preference of P. xylostella was studied with 17 plant species of known glucosinolate content that were compared to Arabidopsis thaliana L. in two-choice tests. Our research shows that the diet on which P. xylostella has fed hardly affects multiple-choice host-plant preference, abaxial and adaxial oviposition preference, or oviposition response to pure glucosinolates. Our study also shows that glucosinolate content affects larval preference, which together with the known correlation between glucosinolate content and P. xylostella oviposition, indicates that crops with high glucosinolate content could be more susceptible to damage by P. xylostella than crops with low glucosinolate content. These findings are discussed in regards to their significance in the management of P. xylostella.